Sexual Partner Characteristics, Relationship Type, and HIV Risk Among a Community Venue–Based Sample of Urban Adolescent and Young Adult Men Who Have Sex With Men. Issue 2 (March 2019) - Boyer, Cherrie B.; Greenberg, Lauren; Korelitz, James; Harper, Gary W.; Stewart-Campbell, Rachel; Straub, Diane; Sanders, Renata; Reid, Lisa-Henry; Futterman, Donna; Lee, Sonia; Ellen, Jonathan M.; ,
Few studies have examined sexual partnerships and HIV risk in diverse samples of African American/Black and Hispanic/Latino adolescent and young adult men who have sex with men (YMSM), a group that have a high burden of HIV in the United States. A community–venue recruitment approach was used, which identified significant differences in HIV risk by sexual partner type among 1, 215 YMSM. Those with casual partners had a higher number of sexual partners, had more sexually transmitted infections (STIs), were more likely to engage in transactional sex, and to use alcohol, marijuana, or other substances compared with those with main partners only. Among those with female sexual partners, many used condoms "every time" when engaging in vaginal sex with casual partners, but a sizable proportion "never/rarely" used condoms with their main partners. Our findings demonstrate a need for tailored HIV prevention education and counseling with necessary skills regarding consistent and correct condom use with all sexual partnerships.